Desigualdade regional e os fundos constitucionais de financiamento no Brasil - Heder Carlos de Oliveira (2005)
There is considerable evidence to demonstrate that the regional development in developing countries shows high level of spatial concentration. The propose of this thesis is to analyze the Brazilian case to identify if the Brazilian Constitutional Funds (FNO, FNE and FCO) have a positive impact on the regional inequality. These funds was created in 1989 in order to finance economic activities in the North, Northeast and Center-West regions. Our results show that regional growth in Brazil over the last 10 years has not been affected by these Constitutional Funds. On the other way, public infra-structure, education and health have a positive relation with regional growth, which suggests that the public expending on those funds should be directed to these regional attributes.